Development of inkjet printed strain sensors - Correia, Vítor (2013)
Strain sensors with different architectures such as single sensors, sensor array and matrix have been developed by inkjet printing technology. Sensors with gauge factors up to 2.48, dimensions of 1.5 mm x 1.8 mm with interdigitated structures with a distance of 30 µm between the finger lines have been achieved based on PeDOT (poly(3,4-ethylenedioxythiophene) and conductive ink. Strain gauges based on silver ink have been also achieved with a gauge factor of 0.35. Performance tests including 1000 mechanical cycles have been successfully carried out for the development of smart prosthesis applications.